2016
DOI: 10.1159/000443845
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Sclerostin Levels Are Associated with a Better Outcome in Haemodialysis Patients

Abstract: Background: Sclerostin is an osteocyte hormone that decreases osteoblastogenesis. Sclerostin may play a key role in osteoporosis and also in vascular calcification (VC). In chronic kidney disease and haemodialysis (HD) patients, serum sclerostin levels are high. Aim: To assess the correlation of serum sclerostin levels with VC, bone mineral density (BMD), and survival rate in HD patients. Methods: A cross-sectional study was conducted in prevalent HD patients to correlate serum sclerostin tertiles with the Kau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Some showed that serum sclerostin levels had no association with all-cause mortality [21][22][23], and two showed a significant negative association with all-cause mortality [24,25]. A recent quantitative meta-analysis concluded that no significant association existed between sclerostin levels and either all-cause mortality or CVD mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some showed that serum sclerostin levels had no association with all-cause mortality [21][22][23], and two showed a significant negative association with all-cause mortality [24,25]. A recent quantitative meta-analysis concluded that no significant association existed between sclerostin levels and either all-cause mortality or CVD mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this research project may suggest that CKD and RRT disturb the assessed parameters. Sato et al and Jean et al observed a positive correlation between SCL levels and BMI values in hemodialyzed patients [11,38]. Pelletier et al demonstrated a positive correlation between SCL levels and BMI values in a group of nonhemodialyzed CKD patients [38].…”
Section: Discussionmentioning
confidence: 96%
“…Increased sclerostin levels (SCL) are first observed at stage III CKD. In patients with end-stage renal disease, sclerostin concentrations are several-fold higher than those in subjects with normal renal function [7][8][9][10][11][12]. Bone metabolism disorders may result in blood vessel calcifications, atherosclerosis, or myocardial ischemia [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have demonstrated that circulating sclerostin levels are positively correlated with better survival in patients undergoing hemodialysis [9]. Nevertheless, other studies have shown that higher serum sclerostin levels increase all-cause mortality in patients with chronic kidney disease (CKD) [10].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%